Agricultural biogas plants in Eastern Hungary - Kith, Károly (Acta Agraria Debreceniensis, 2015)
In the scope of the article, agricultural biogas plants which operate within the region have been analysed together with their linked livestock plants. The study attempts to describe the current condition and future opportunities of the sites. It also covers the description of energy production/use efficiency. The study contains the list of factors determining the economic operation of biogas plants. In the course of the analysis, types, amount and quality of energy produced of different raw materials have been determined within the decentralised energy production.